2020
DOI: 10.1111/clr.13687
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic changes in height and volume after lateral GBR procedures with different ratios of deproteinized bovine bone mineral and autogenous bone at different time points. An experimental study

Abstract: Objective Estimate changes in augmentation height and volume after lateral guided bone regeneration (GBR) augmentation with different ratios of deproteinized bovine bone mineral (DBBM) and particulate autogenous bone (PAB) and autogenous bone block (ABB), at different time points. Material and methods Twenty‐four minipigs were randomly allocated into three healing periods. Lateral augmentation in 96 sites with standardized quantity of graft material was performed with different ratios of DBBM and PAB (50:50, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…This finding is in line with previously reported outcomes of another preclinical study in a canine model, which revealed that adding autogenous bone to DBBM did not confer an advantage over grafting with DBBM alone in terms of the amount of the newly formed bone measured in the late healing phase, in spite of an accelerated new bone formation in the early stage (Janner et al., 2017). The findings are also supported by a recent preclinical study in minipigs, in which the outcome did not differ significantly regardless of the ratio of autogenous bone particles to xenograft materials (Aludden et al., 2020). Despite the fact that the NBAs of the two groups were almost the same, %NBA was slightly higher (not statistically significant) in the DBBM/Auto group compared to the DBBM group, which seemed to be because the RA which was a denominator in calculating %NBA was approximately 20% higher in the DBBM group compared with the DBBM/Auto group.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This finding is in line with previously reported outcomes of another preclinical study in a canine model, which revealed that adding autogenous bone to DBBM did not confer an advantage over grafting with DBBM alone in terms of the amount of the newly formed bone measured in the late healing phase, in spite of an accelerated new bone formation in the early stage (Janner et al., 2017). The findings are also supported by a recent preclinical study in minipigs, in which the outcome did not differ significantly regardless of the ratio of autogenous bone particles to xenograft materials (Aludden et al., 2020). Despite the fact that the NBAs of the two groups were almost the same, %NBA was slightly higher (not statistically significant) in the DBBM/Auto group compared to the DBBM group, which seemed to be because the RA which was a denominator in calculating %NBA was approximately 20% higher in the DBBM group compared with the DBBM/Auto group.…”
Section: Discussionsupporting
confidence: 72%
“…A recent preclinical study also demonstrated increased bone formation with the addition of autogenous bone chips in the early healing phase, whereas new bone formation was similar in the later healing phase regardless of the use of autogenous bone chips (Janner et al, 2017). This latter finding was corroborated by evidence from a recent randomized clinical trial showing that increasing the proportion of autogenous bone chips did not enhance histologic bone formation in a horizontal defect treated with GBR (Aludden et al, 2020). Similar clinical outcomes have been described for other randomized clinical trials, but these were associated with an increased risk of complications related to the donor sites (Patel et al, 2019;Temmerman et al, 2020).…”
Section: Introductionmentioning
confidence: 78%
“…However, two-dimensional linear clinical or radiographic measurements were used in all the included studies of the present systematic review revealing a non-significant tendency to increased gain in alveolar ridge width and diminish postoperative resorption with the use of barrier membrane coverage [18,[33][34][35]. High degree of reliability, accuracy and reproducibility in quantifying volumetric changes of the augmented area following LARA with the use of three-dimensional computer software have previous been reported in clinical and experimental studies [44,45]. A previous study using threedimensional volumetric assessment of the augmented area following LARA with an autogenous bone block graft alone from the iliac crest without barrier membrane coverage revealed a volume reduction of the augmented area by 78%, whereas two-dimensional linear measurements disclosed an alveolar ridge reduction from 11,2 mm to 5,6 mm corresponding to 50%, after two years [46].…”
Section: Discussionmentioning
confidence: 95%
“…The sample size was calculated with an assumed power of 80% (using α = 0.05) to detect a minimal mean percentage and standard deviation of 27. 30…”
Section: Sample Size Calculationmentioning
confidence: 99%